Optimal gestational weight gain in Chinese pregnant women with gestational diabetes mellitus: A large retrospective cohort study. Issue 1 (2nd October 2022) - Fan, Xiaoxiao; Dai, Jiamiao; He, Jing; Tian, Ruixue; Xu, Jingqi; Song, Jiayang; Bai, Jinbing; Liu, Yanqun; Zou, Zhijie; Chen, Xiaoli
Abstract: Aim: To examine the optimal gestational weight gain (GWG) for Chinese pregnant women with gestational diabetes mellitus (GDM) based on the Chinese‐specific body mass index (BMI) classification. Methods: A retrospective cohort study was conducted using the 2017–2020 data from pregnant women with GDM in a tertiary hospital. A quadratic function model and the total predicted probability of adverse pregnancy outcomes were developed to obtain the optimal GWG. Differences in the incidence of adverse pregnancy outcomes between our optimal GWG recommendations and the Institute of Medicine (IOM) 2009 GWG guidelines were also analyzed. Results: A total of 8103 pregnant women with GDM were analyzed. Based on the Chinese‐specific BMI classification, the optimal GWG range was 11.0–17.5 kg for underweight women, 3.7–9.7 kg for normal‐weight women, −0.6 to 4.8 kg for overweight women, and − 9.8 to 4.2 kg for obese women. Excessive GWG had a higher risk of large for gestational age (LGA) (OR: 2.99, 95% CI: 2.42–3.70), macrosomia (OR: 2.35, 95% CI: 1.77–3.12), pre‐eclampsia (OR: 1.91, 95% CI: 1.37–2.65), gestational hypertension (OR: 1.65, 95% CI: 1.24–2.19), cesarean section (OR: 1.29, 95% CI: 1.15–1.44), postpartum hemorrhage (OR: 1.29, 95% CI: 1.02–1.64); insufficient GWG had a higher risk of small for gestational age (OR: 1.82, 95% CI: 1.20–2.75). Compared to the IOM 2009 GWG guidelines, the prevalence of macrosomia, LGA, and postpartum hemorrhage were significantly lower in pregnant women following the implementation of our recommended GWG range ( p < 0.05). Conclusions: Compared to the IOM 2009 GWG recommendations, our optimal GWG recommendations for Chinese pregnant women were more sensitive.